1979
DOI: 10.1002/mpo.2950060311
|View full text |Cite
|
Sign up to set email alerts
|

A comparative trial of daunorubicin, cytosine arabinoside, and thioguanine, and a combination of the three agents for the treatment of acute myelocytic leukemia

Abstract: In this study 523 previously untreated patients with acute myelocytic leukemia were randomly allocated to induction therapy with daunorubicin 60 mg/M2 daily X 3, cytosine arabinoside and thioguanine 100 mg/M2 each every 12 hours until marrow hypoplasia was achieved, or a 5-day course of the three drugs with daunorubicin 100 mg/M2 given on dav 1 and cytosine arabinoside plus thioguanine each given at a dose of 100 mg/M2 every 12 hours for five days. All patients received cyclophosphamide 600 mg/M2 followed in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Death during induction (other failures) was twice as common a cause of induction failure as was clinically documented drug-resistant disease. The 4.5-month median duration of unmaintained remission achieved in the present study is reminiscent of earlier trials in which patients received inadequate consolidation/maintenance therapies and attained remission durations of only several months [2,10,11]. It is of interest that in spite of the short median duration of remission, two patients attained remission durations of greater than 90 weeks, suggesting that there exists a subset of patients who do not require any therapy after entering remission and who nevertheless attain prolonged remission durations.…”
Section: Discussionsupporting
confidence: 66%
“…Death during induction (other failures) was twice as common a cause of induction failure as was clinically documented drug-resistant disease. The 4.5-month median duration of unmaintained remission achieved in the present study is reminiscent of earlier trials in which patients received inadequate consolidation/maintenance therapies and attained remission durations of only several months [2,10,11]. It is of interest that in spite of the short median duration of remission, two patients attained remission durations of greater than 90 weeks, suggesting that there exists a subset of patients who do not require any therapy after entering remission and who nevertheless attain prolonged remission durations.…”
Section: Discussionsupporting
confidence: 66%
“…There has been substantial improvement in the treatment of patients with AML over the last decade, with reported remission rates of 58% to 90%.". 12 The impact of such improved treatments on patients with high leukocyte counts is not established, and it is not known to what degree extreme leukocytosis is still a significant adverse prognostic factor. Since the currently available therapeutic agents are effectively applied to the management of leukemia in adults, identification of "highrisk" patient groups, and definition of natural history and causes of treatment failure of these groups, is of major importance.…”
Section: Leukocyte Count Of Over 1ooooo/p1 In Patientsmentioning
confidence: 99%
“…In several trials, remission rates of 50-82% have been reported with the standard combination of daunorubicin, cytarabine with or without 6-thioguanine (DAT) [22][23][24]. Similarly, the substitution of 6-thioguanine for etoposide is synergistic in vitro and was effective in prolonging remission duration in younger patients [6].…”
Section: Discussionmentioning
confidence: 99%